The Impact Of Gender And Gender Composition On Occupational Wage Inequality In Palestine: A Multilevel Modeling Approach - Ayyash, Mohsen H.H. (2021)
Inequality in the wage paid between males and females is a global phenomenon faced by the world. The problem is more severe in developing countries due to the social-cultural factor. Palestine is one of the countries experiencing a high ratio of imbalance participation rate of genders in the labor market in which female participation is among the lowest worldwide. On the other hand, occupational discrimination and wage inequality still exist between males and females. Combining both issues, this thesis seeks to examine the impact of gender and occupational gender composition on wage levels in the Palestinian labor market and contributes in three ways: first, this is the first study that analyzes the occupational gender wage gap in Palestine using multilevel linear models due to its high ratio of the gender pay gap. It does not limit the investigation of the betweenoccupation groups and within-occupation groups variations but also includes the examination between-gender-within occupation groups wage differentials. Second, this thesis demonstrates that the Bayesian estimator provides the most accurate and efficient estimation as compared to the conventional technique of maximum likelihood (ML) and restricted maximum likelihood (RML). Third, the thesis examines the effect of occupational sex segregation by utilizing the two-level wage models where occupations classification is decomposed using an ISCO-08 twodigit classification.This approach provides a more accurate estimate but not yet well-explored. The data are collected from the Palestinian Labour Force Survey (PLFS) over the period 2014 to 2018. The results reported evidence of wage inequality due to occupational groups which account for about 23.4% of wage differentials. On average, wages in male-dominated occupations are higher than those in gender-integrated and female-dominated occupations, which supports the devaluation hypothesis. The results also indicate that men enjoyed wage advantage over women across the gender-typed occupations, which supports the universal male advantage hypothesis. Moreover, the size of the gender pay gap is wider in occupations dominated by females as compared to other gender-typed occupations. Besides gender-based occupational discrimination, a significant portion of the between-occupation wage gap in the Palestinian labor market is mainly explained by workers’ characteristics including place of work, industrial sectors, sector of employment, region, work status, and marital status. The thesis suggests reducing the gender wage gap through equal pay enforcement and programs to encourage women's participation in the labor market.